Unnecessary contraindications for mobile-bearing unicompartmental knee replacement. - Pandit, H; Jenkins, C; Gill, H; Smith, G; Price, A; Dodd, C; Murray, D (2011)
The contraindications for unicompartmental knee replacement (UKR) remain controversial. The views of many surgeons are based on Kozinn and Scott's 1989 publication which stated that patients who weighed more than 82 kg, were younger than 60 years, undertook heavy labour, had exposed bone in the patellofemoral joint or chondrocalcinosis, were not ideal candidates for UKR. Our aim was to determine whether these potential contraindications should apply to patients with a mobile-bearing UKR. In order to do this the outcome of patients with these potential contraindications was compared with that of patients without the contraindications in a prospective series of 1000 UKRs. The outcome was assessed using the Oxford knee score, the American Knee Society score, the Tegner activity score, revision rate and survival. The clinical outcome of patients with each of the potential contraindications was similar to or better than those without each contraindication. Overall, 678 UKRs (68%) were performed in patients who had at least one potential contraindication and only 322 (32%) in patients deemed to be ideal. The survival at ten years was 97.0% (95% confidence interval 93.4 to 100.0) for those with potential contraindications and 93.6% (95% confidence interval 87.2 to 100.0) in the ideal patients. We conclude that the thresholds proposed by Kozinn and Scott using weight, age, activity, the state of the patellofemoral joint and chondrocalcinosis should not be considered to be contraindications for the use of the Oxford UKR.